2012
DOI: 10.1002/ejic.201200115
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Tricarbonylmanganese Photoactivatable CO Releasing Molecules (PhotoCORMs) by Using the Myoglobin Assay and Time‐Resolved IR Spectroscopy

Abstract: Tricarbonylmanganese(I) complexes of the ligands tris(imidazol-4-yl)phosphane (4-tip H ), tris(1,4-diisopropylimidazol-2yl)phosphane (2-tip iPr2 ), tris(pyridin-2-yl)phosphane (tpp) and tris(N-methylimidazol-2-yl)carbinol (2-tic NMe ) were prepared. These act as N,N,N tripodal chelators. The solid-state structure of [Mn(CO) 3 (tpp)]OTf was determined by X-ray diffraction. The potential of these complexes to act as photoactivatable CO-releasing molecules (PhotoCORMs) was studied with the UV/Vis spectroscopy-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 61 publications
(36 reference statements)
1
29
0
2
Order By: Relevance
“…The formation of Mb‐CO is quantified and correlated to the amount of CO released by the CORM. However, this assay suffers from several drawbacks,4042 and modifications have been proposed 43. The strong absorbance of myoglobin in the near‐UV and visible regions makes the assay incompatible with photolysis in aerated media, and limits the utility of the technique for quantifying CO release by photoCORMs.…”
Section: Current Limitations For the Clinical Use Of Cormsmentioning
confidence: 99%
“…The formation of Mb‐CO is quantified and correlated to the amount of CO released by the CORM. However, this assay suffers from several drawbacks,4042 and modifications have been proposed 43. The strong absorbance of myoglobin in the near‐UV and visible regions makes the assay incompatible with photolysis in aerated media, and limits the utility of the technique for quantifying CO release by photoCORMs.…”
Section: Current Limitations For the Clinical Use Of Cormsmentioning
confidence: 99%
“…Functionalization of manganese complexes with peptides offers potential for the selective delivery of CO-releasing manganese complexes to cells [26]. Time-resolved IR spectroscopy is powerful for monitoring the release of CO from these complexes [27]. …”
Section: Photo-induced Release Of Bioactive Moleculesmentioning
confidence: 99%
“…2 An attractive family of CORMs liberate CO upon illumination (so-called photo-CORMs) and numerous studies of such substances can be found in the literature reporting the amount and kinetics of the CO release, the targeting of specific body tissues and the wavelength needed to trigger CO release. [3][4][5] In this work, we focus on [Mn I (CO) 3 (κ 3 -L)] compounds, manganese(I) complexes whose photoCORM-activities have been studied for many years. However, details concerning the reaction sequence leading to CO release, the role of manganese redox chemistry in the process or the Mn-containing products of the photoreaction are still scarce.…”
Section: Introductionmentioning
confidence: 99%